Relevance of student representative councils in Malaysian Higher Education: The Case of Universiti Utara Malaysia - Emina Kulasic Bong Ei Min (Penerbit Universiti Kebangsaan Malaysia, 2024)
This research paper explores the relevance of student representative councils (SRCs) in higher education institutions with a specific focus on Universiti Utara Malaysia. By analyzing the functions, effectiveness, and contributions to student engagement and campus life, this study aims to provide insights into the meaningful role SRCs play in shaping the student experience and fostering a vibrant campus community. This study will also take into consideration the general opinion of students toward the significance of the SRC body and attempt to redefine the capacity of such an entity. The study uses first and secondary qualitative data to obtain the results. The results found that SRC institutions were still relevant in Malaysian universities if there is a quick response rate in solving student issues.